Traffic Accident Criminal Offence Due to Over Dimension Overload on Goods Transport Vehicles - Muhar Irwansyah, Joko; Zarzani, Riza (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This article analyzes the criminal liability of traffic accidents caused by Over Dimension Overload (ODOL) in goods transport vehicles. ODOL practices lead to increased road damage, traffic congestion, and higher accident rates, posing significant safety risks to both vehicles and public infrastructure. The research focuses on case number 49/Pid.Sus/2022/Pn-Idi, in which a logistics company was convicted for modifying a truck and violating load capacity regulations. The study explores the legal framework regulating vehicle dimensions and load limits in Indonesia, and examines the enforcement of these laws, particularly the challenges in controlling ODOL practices despite existing regulations. The results highlight the need for stricter enforcement and clearer legal standards to ensure road safety and reduce infrastructure damage.